Assessing the Difficulty and Long-Term Retention of Factual and Conceptual Knowledge Through Multiple-Choice Questions: A Longitudinal Study - Haycocks NG; Hernandez-Moreno J; Bester JC; Hernandez Jnr R; Kalili R; Samrao D; Simanton E; Vida TA (Advances in Medical Education and Practice)
Neil G Haycocks,1,2 Jessica Hernandez-Moreno,3 Johan C Bester,4 Robert Hernandez Jnr,3 Rosalie Kalili,3 Daman Samrao,3 Edward Simanton,3 Thomas A Vida3 1Department of Pathology, University of Utah School of Medicine, Salt Lake City, UT, USA; 2Utah Office of the Medical Examiner, Taylorsville, UT, USA; 3Department of Medical Education, Kirk Kerkorian School of Medicine at UNLV, Las Vegas, NV, USA; 4Office of Curricular Affairs and Department of Family and Community Medicine, Saint Louis University School of Medicine, Saint Louis, MO, USACorrespondence: Thomas A Vida, Email thomas.vida@unlv.eduPurpose: Multiple choice questions (MCQs) are the mainstay in examinations for medical education, physician licensing, and board certification. Traditionally, MCQs tend to test rote recall of memorized facts. Their utility in assessing higher cognitive functions has been more problematic to determine. This work evaluates and compares the difficulty and long-term retention of factual versus conceptual knowledge using multiple-choice questions in a longitudinal study.Patients and Methods: We classified a series of MCQs into two groups to test recall/verbatim and conceptual/inferential thinking, respectively. We used the MCQs to test a two-part hypothesis: 1) scores for recall/verbatim questions would be significantly higher than for concept/inference questions, and 2) memory loss over time would be more significant for factual knowledge than conceptual understanding compared with a loss in the ability to reason about concepts critically. We first used the MCQs with pre-clinical medical students on a summative exam in 2020, which served as a retrospective benchmark of their performance characteristics. After two years, the same questions were re-administered to volunteers from the same cohort of students in 2020.Results: Retrospective analysis revealed that recall/verbatim questions were answered correctly more frequently (82.0% vs 60.9%, P = 0.002). Performance on concept/inference questions showed a significant decline, but a larger decline was observed for recall/verbatim questions after two years. Performance on concept/inference questions showed a slight decline across quartiles, while two years later, recall/verbatim questions experienced substantial performance loss. Subgroup analysis indicated convergence in performance on both question types, suggesting that the clinical relevance of the MCQ content may have influenced a regression toward a baseline mean.Conclusion: These findings suggest conceptual/inferential thinking is more complex than rote memorization. However, the knowledge acquired is more durable in a longitudinal fashion, especially if it is reinforced in clinical settings.Keywords: medical education assessment, multiple choice questions (MCQs), long-term knowledge retention, conceptual learning, cognitive function testing